Inclusion of In-Situ Velocity Measurements into the UCSD Time-Dependent Tomography to Constrain and Better-Forecast Remote-Sensing Observations - Jackson, B. V.; Hick, P. P.; Bisi, M. M.; Clover, J. M.; Buffington, A. (Solar Physics, 2010)
The University of California, San Diego (UCSD) three-dimensional (3-D) time-dependent tomography program has been used successfully for a decade to reconstruct and forecast coronal mass ejections from interplanetary scintillation observations. More recently, we have extended this tomography technique to use remote-sensing data from the Solar Mass Ejection Imager (SMEI) on board the Coriolis spacecraft; from the Ootacamund (Ooty) radio telescope in India; and from the European Incoherent SCATter (EISCAT) radar telescopes in northern Scandinavia. Finally, we intend these analyses to be used with observations from the Murchison Widefield Array (MWA), or the LOw Frequency ARray (LOFAR) now being developed respectively in Australia and Europe. In this article we demonstrate how in-situ velocity measurements from the Advanced Composition Explorer (ACE) space-borne instrumentation can be used in addition to remote-sensing data to constrain the time-dependent tomographic solution. Supplementing the remote-sensing observations with in-situ measurements provides additional information to construct an iterated solar-wind parameter that is propagated outward from near the solar surface past the measurement location, and throughout the volume. While the largest changes within the volume are close to the radial directions that incorporate the in-situ measurements, their inclusion significantly reduces the uncertainty in extending these measurements to global 3-D reconstructions that are distant in time and space from the spacecraft. At Earth, this can provide a finely-tuned real-time measurement up to the latest time for which in-situ measurements are available, and enables more-accurate forecasting beyond this than remote-sensing observations alone allow.